2018
DOI: 10.2217/epi-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferases and Gastric Cancer: Insight Into Targeted Therapy

Abstract: Gastric cancer is a major health problem worldwide occupying most frequent causes of cancerrelated mortality. In addition to genetic modifications, epigenetic alterations catalyzed by DNA methyltransferases (DNMTs) is a well-characterized epigenetic hallmark in gastric cancer. The reversible nature of epigenetic alterations and central role of DNA methylation in diverse biological processes provides an opportunity for using DNA methyltransferase inhibitors to enhance the efficacy of chemotherapeutics. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 187 publications
0
24
0
Order By: Relevance
“…DNA methylation is catalyzed by three DNMTs, DNMT1, DNMT3A, and DNMT3B, which all add a methyl group to the C5 position of the cytosine ring of the DNA to produce 5-methylcytosine (5-mC). DNMT1 mediates maintenance DNA methylation, whereas DNMT3a and 3b mediate de novo DNA methylation 24 . This methylation process is reversible by DNA demethylases, TET1, TET2, and TET3.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is catalyzed by three DNMTs, DNMT1, DNMT3A, and DNMT3B, which all add a methyl group to the C5 position of the cytosine ring of the DNA to produce 5-methylcytosine (5-mC). DNMT1 mediates maintenance DNA methylation, whereas DNMT3a and 3b mediate de novo DNA methylation 24 . This methylation process is reversible by DNA demethylases, TET1, TET2, and TET3.…”
Section: Resultsmentioning
confidence: 99%
“…GC is one of the most common malignancies, causing one of the highest public health burdens[ 1 , 20 ]. Studies have shown that GC carcinogenesis is a multistep and multifactorial process caused by genetic changes and epigenetic alterations[ 2 , 21 ]. GC is characterized by accumulated genomic modifications, including somatic mutations and genomic amplifications and deletions[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…GC is characterized by accumulated genomic modifications, including somatic mutations and genomic amplifications and deletions[ 22 ]. However, evidence has shown that both genomic aberrations and Helicobacter pylori -induced precursors are associated with multiple epigenetic changes, such as hypermethylation of tumor suppressors and hypomethylation of oncogenes[ 12 , 21 ]. For instance, Helicobacter pylori can induce methylation of multiple CpG islands in GC patients, which subsequently increases genome instability by stimulating activation-induced cytidine deaminase or altering microRNA expression[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, further studies are needed to better understand the interaction of epigenetic treatments and radiation therapy, given that these interesting results seem to be cell-type associated. Thus, despite the described side effects of epigenetic agents [ 140 ], the combination of these with chemo- and radiotherapy is a promising strategy and a hot topic for GC treatment, to maximize the potential of cytotoxic agents and radiation therapy. In recent years, non-nucleoside epigenetic compounds are attracting growing interest, because of their lower toxicity and the ability to bind and inhibit the catalytic domain of DNMTs, without integrating in DNA, and thus avoiding the non-specific effects of nucleoside analogues [ 102 ].…”
Section: Current and New Epigenetic Strategies For Gastric Cancer mentioning
confidence: 99%